EFSA FoodEx2 Interpreting and Checking Tool user guide. Issue 11 (6th November 2019) - ,; Ioannidou, Sofia
Abstract : The EFSA FoodEx2 Interpreting and Checking Tool is a Microsoft Excel ® spreadsheet, developed by the Evidence Management Unit of the European Food Safety Authority as an add‐on the EFSA Catalogue browser. It is able to analyse and interpret FoodEx2 codes generated with the EFSA Catalogue browser. More specifically, the main purpose of the tool is to provide a complete description of the FoodEx2 code in English, and check its quality by using the dedicated business rules. This will assist data providers in performing a quality check of the selected FoodEx2 codes before sending their datasets to EFSA. Both interpretation and quality check processes are achieved due to the direct linkage of the tool with the Catalogue browser. The installation process of the Interpreting and Checking Tool depends on both the operating system and the version of the Catalogue browser installed